Analisis Portofolio Optimal : Pendekatan Mean Variance Pada Harga Komoditas Pangan di Kota Padang - Elfa Rafulta -; Roni Tri Putra (Jurnal Ilmiah Poli Rekayasa, 2020)
Investment is a number of commitments or a number of funds or resources made at this time with the aim of obtaining future profits. One method that can be used to form an optimal portfolio is to use the mean variace approach. Asset selection is carried out on food commodities namely rice, eggs, cooking oil, granulated sugar, and red chili. From the data processing it is found that the weight of each commodity is cooking oil (99.95%), eggs (0.03%), granulated sugar (0.04%), red chili is negative (-0.02%), and rice (0.00%). So that it can be estimated that the expected profit is -0.0024% and risk is 0.0001%.